Scanning Kelvin probe microscopy on organic field-effect transistors during gate bias stress - Mathijssen, Simon G. J.; Cölle, Michael; Mank, A. J. G.; Kemerink, Martijn; Bobbert, Peter A.; Leeuw, Dago M. de (Applied physics letters, 2007)
The reliability of organic field-effect transistors is studied using both transport and scanning Kelvin probe microscopy measurements. A direct correlation between the current and potential of a ppp-type transistor is demonstrated. During gate bias stress, a decrease in current is observed, that is correlated with the increased curvature of the potential profile. After gate bias stress, the potential changes consistently in all operating regimes: the potential profile gets more convex, in accordance with the simultaneously observed shift in threshold voltage. The changes of the potential are attributed to positive immobile charges, which contribute to the potential, but not to the current.
Gesehen am 11.12.2019